Dakwah Kontemporer dan Teknologi Informasi di Dunia Pendidikan Pondok Pesantren - Suaeb Qury (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2024)
The development of information and communication technology has brought significant changes in da'wah methods, allowing the spread of Islamic teachings through social media, applications, and e-learning platforms. This study uses a qualitative approach to analyze how information technology changes da'wah methods, scholars' views on digital da'wah, and the effectiveness of social media platforms in da'wah. The results of the study show that digital da'wah is able to reach a wider audience and provide religious education flexibly, especially among the younger generation who are more familiar with technology. However, there are challenges in maintaining the authenticity and accuracy of Islamic teachings and preventing the spread of misinformation. Islamic scholars and institutions support the use of technology in da'wah as long as it remains in accordance with Islamic principles. Social media platforms, da'wah applications, webinars, and podcasts have become important tools in modern da'wah, increasing the appeal and effectiveness of spreading Islamic teachings. The importance of integrating technology with a strategic and ethical approach in contemporary da'wah to ensure the relevance and effectiveness of da'wah in modern society and strengthen religious education through digital media. Islamic boarding schools also play an important role in implementing information technology to support more dynamic and interactive religious education.